OPTIMASI PROSES PEMBUATAN METIL ESTER SULFONAT DARI MINYAK INTI SAWIT - Sri Hidayati, Ani Suryani, Puji Permadi, Erliza Hambali, Khaswar Syamsu dan Sukardi (Jurnal Teknologi Industri Pertanian, 2005)
ABSTRACTMethyl Ester Surfactant (MES) is produced from sulphonation process between methyl ester and sulphonating agent, such as NaHCO3.  This research aim was to find the condition of optimum process to produce in MES surfactant.   The analysis of resulted response surface indicated that the optimum conditions of MES production from methyl ester of PKO was obtained at reaction temperature of 96,5oC, sulphonation reaction time of 4,3 hour, methanol concentration of 26,6%, and purification temperature of 45,5oC with IFT of 0,23 dyne/cm, surface tension of 32,8 dyne/cm, emulsion stability of 88,7%, acid value of 16,32 mg KOH/g sample, Iodine value of 7,84 Iod g/100 sample,  peroxide value of 9,8 mmole/1000 gram,  and sulphonates absorbance of 1,51 AU.Key words:  methyl ester sulphonates, palm kernel oil, optimization, sulphonation